If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4r-2=(r-6)
We move all terms to the left:
4r-2-((r-6))=0
We calculate terms in parentheses: -((r-6)), so:We get rid of parentheses
(r-6)
We get rid of parentheses
r-6
Back to the equation:
-(r-6)
4r-r+6-2=0
We add all the numbers together, and all the variables
3r+4=0
We move all terms containing r to the left, all other terms to the right
3r=-4
r=-4/3
r=-1+1/3
| 7/9v=28 | | (2a+4)=(3a-8) | | 2.4=t4.5 | | 2x-16x-80=4 | | -3p+4=12 | | 3(3x-2)-9x+5=0 | | 27x+5=15x-2 | | 2m-3=-12 | | 16y2=25 | | 4x+6+2x+17=7x+4 | | 10m-5m=45 | | 4x^2+3x^2=75 | | 9+3y+-2y=14 | | 22y=125614 | | 4^x-10=0 | | 6x-5x=3x-29 | | 2n^2-11n=-9 | | 16m+5m-11m=20 | | x/5=8/90 | | x/5=90/8 | | 19/20=p/6 | | 8x-45=7x-17 | | x/1.00-x=4 | | 5/x=8/90 | | y=4+2/3/180 | | (4x-7)={5(x+4) | | 5/x=90/8 | | y=4+2/3 | | 2x+150+x=180 | | 2n^2-2=6 | | √x+2+4=6 | | (5y+6)=(14y-36) |